Comparative electron microscopic study of the stomach of Orchestia cavimana and Arcitalitrus sylvaticus (Crustacea: Amphipoda) - Štrus, Jasna; Storch, Volker (Journal of morphology, 2004)
The functional morphology of stomachs of the European semiterrestrial amphipod Orchestia cavimana and of the Australian terrestrial species Arcitalitrus sylvaticus was studied by electron microscopy. The stomach of the two amphipod species is divided longitudinally into a spacious dorsal food channel and two ventral filtration channels. Additionally, a prominent helically oriented circulation channel is situated on each lateral side of the stomach, forming a semicircular channel separated from the food channel by spines. The food channel conveys coarse food particles directly into the midgut through a funnel. The filtration channels receive fine material filtered through primary and secondary filters. Material forced through the secondary filters by the pressure of the laterally located inferolateralia eventually reaches the openings of the midgut glands. Washing of filters and soaking of ingested food items with enzymes probably is achieved by a forward stream of digestive juice from the midgut glands and conveyed through the circulatory channels. The specializations of the stomach of the two species of Amphipoda investigated are described and compared to the pertinent structures of Mysidacea and Isopoda. J. Morphol. 259:340-346, 2004. © 2004 Wiley-Liss, Inc.